Rancang Bangun Multi Frekuensi Rectenna Untuk Energy Harvesting Gelombang Elektromagnetik - Sukriyah Buwarda; Asmawaty Azis (PROtek : Jurnal Ilmiah Teknik Elektro, 2021)
The increasing need for electrical energy encourages the birth of methods to utilize various forms of energy available in nature called energy harvestin. One of them is from electromagnetic waves that are massif used daily by the community. In this study, a rectifier antenna (rectenna) was created using a 5-stage voltage doubler method with the aim of generating DC electrical energy from the input of electromagnetic waves that propagate freely in the air. Electromagnetic waves are captured using two types of antennas with the aim of capturing different frequencies, namely UHF TV antennas with a working frequency of 470-806 MHz and WiFi antennas with a working frequency of 2400 MHz commonly used by the public. Because testing is conducted in open spaces, where environmental change conditions greatly affect the captured electromagnetic geombang encroachment, DC electrical power tends to change during testing. The largest DC electricity generated by WiFi antenna input is 1,420V and the average voltage is 231.7mV/min with a distance of 90cm from the largest frequency source and UHF TV antenna is 648mV and the average voltage is 478.16mV/min with a distance of 0 cm from the largestfrequency source